Genome-wide mapping of Piwi association with specific loci in Drosophila ovaries - Liu, Na; Neuenkirchen, Nils; Zhong, Mei; Lin, Haifan (G3 : genes - genomes - genetics, 2021)
Small noncoding RNA pathways have been implicated in diverse mechanisms of gene regulation. In Drosophila ovaries, Piwi binds to Piwi-interacting RNAs (piRNAs) of mostly 24–28 nucleotides (nt) and plays an important role in germline stem cell maintenance, transposon repression, and epigenetic regulation. To understand the mechanism underlying these functions, we report the application of the DamID-seq method to identify genome-wide binding sites of Piwi in Drosophila ovaries. Piwi localizes to at least 4535 euchromatic regions that are enriched with piRNA target sites. Surprisingly, the density of Piwi binding to euchromatin is much higher than in heterochromatin. Disrupting the piRNA binding of Piwi results in an overall change of the genomic binding profile, which indicates the role of piRNAs in directing Piwi to specific genomic sites. Most Piwi binding sites were either within or in the vicinity of protein-coding genes, particularly enriched near the transcriptional start and termination sites. The methylation signal near the transcriptional termination sites is significantly reduced when Piwi was mutated to become defective in piRNA binding. These observations indicate that Piwi might directly regulate the expression of many protein-coding genes, especially through regulating the 3' ends of targeted transcripts.